Suppressed Layered‐to‐Spinel Phase Transition in δ‐MnO2 via van der Waals Interaction for Highly Stable Zn/MnO2 Batteries. Issue 12 (4th November 2022) - Qiu, Ce; Liu, Jia; Liu, Hanghui; Zhu, Xiaohui; Xue, Liang; Li, Shuang; Ni, Mingzhu; Zhao, Yang; Wang, Tong; Savilov, Serguei V.; Aldoshin, Sergey M.; Xia, Hui
Abstract: Although birnessite‐type manganese dioxide (δ‐MnO2 ) with a large interlayer spacing (≈7 Å) is a promising cathode candidate for aqueous Zn/MnO2 batteries, the poor structural stability associated with Zn 2+ intercalation/deintercalation limits its further practical application. Herein, δ‐MnO2 ultrathin nanosheets are coupled with reduced graphene oxide (rGO) via van der Waals (vdW) self‐assembly in a vacuum freeze‐drying process. It is interesting to find that the presence of vdW interaction between δ‐MnO2 and rGO can effectively suppress the layered‐to‐spinel phase transition in δ‐MnO2 during cycling. As a result, the coupled δ‐MnO2 /rGO hybrid cathode with a sandwich‐like heterostructure exhibits remarkable cycle performance with 80.1% capacity retained after 3000 cycles at 2.0 A g −1 . The first principle calculations demonstrate that the strong interfacial interaction between δ‐MnO2 and rGO results in improved electron transfer and strengthened layered structure for δ‐MnO2 . This work establishes a viable strategy to mitigate the adverse layered‐to‐spinel phase transition in layered manganese oxide in aqueous energy storage systems. Abstract : Birnessite‐type manganese dioxide (δ‐MnO2 ) ultrathin nanosheets are coupled with reduced graphene oxide (rGO) via van der Waals self‐assembly. It is demonstrated that vdW interaction in the 2D δ‐MnO2 /rGO heterostructure can effectively suppress the layered‐to‐spinel phase transition in δ‐MnO2 during cycling, thus leading to greatly improved cycle performance for the intercalation type aqueous Zn/MnO2 batteries.